New Design of Low Complexity Multipliers in DFT/IDFT - Alwan, Majid A. (Basrah Journal for Engineering Sciences, 2020)
This paper presents a new design to implement DFT/IDFT using the two components of a sequence, which are even and odd component sequences to solve the complexity of complex multiplications and reduce the number of multipliers. The proposed two implementations reduce the number of real multipliers needed to compute the DFT. The first proposed design gives good results for $N 512$ as compared to conventional FFT algorithm, while the second scenario gives good results for $N 1024$ as compared to conventional FFT algorithm. The proposed design is performed directly from real and imaginary part equations of the DFT sequence $X[k]$ without additional processing.